Keeping It Real: Antibiotic Use Problems and Stewardship Solutions in Low- and Middle-income Countries. Issue 3 (March 2022) - Basu, Saurav; Copana, Raul; Morales, Ronaldo; Anugulruengkitt, Suvaporn; Puthanakit, Thanyawee; Maramba-Lazarte, Cecilia; Williams, Phoebe; Musembi, John; Boga, Mwanamvua; Issack, Mohammad; Hokororo, Adolfine; Falade, Adegoke G.; et al.
Abstract : Antimicrobial resistance is a global health threat and there is an urgent need to manage antibiotic use to slow its development. However, antimicrobial stewardship interventions in low- and middle-income countries (LMIC) have been limited in terms of their resourcing, feasibility and effectiveness in the face of greater challenges in child mortality. We sought to gather together examples of antibiotic use problems faced by clinicians in LMIC, many of which are unique to these settings, and real-world antimicrobial stewardship solutions identified, with the goal of learning broader lessons that might be applicable across LMIC.